Social Media Influence on Millennials’ Purchase Intentions for H&M Fashion Items During Covid-19 - Stephanie, Thio Erika; Mutti, Alif Ikrami Bin (Asian Journal of Social and Humanities, 2025)
Since the start of the Covid-19 pandemic epidemic, lockdown has badly impacted and negatively affected the majority of businesses in Malaysia. It had a big impact on the fashion business, especially at H&M. Due to its fashion knowledge and trend spotting abilities, it is one of the largest and fastest growing fashion clothing firms in the world. It is also a fashion brand that millennials find to be highly appealing. It exposed every flaw in the widely-applied conventional business models, particularly those that placed a strong emphasis on the "quick fashion" idea. When considering the unique attributes at the fundamental of the fast fashion business model, such as excessive production waste and the organisational disposal of wastes, which were constrainedly connected with an abundance of supply, the impact on this industry with a highly globalised supply chain was important from an industrial and economic output perspective. Due to their upbringing in an environment where brands and marketing are prevalent, millennials are significantly more brand sensitive and materialistic. The majority of millennials interact with social media platforms often and are receptive to its impact. The quick growth of the social media sector is affecting consumers' purchasing intentions. The goal of this study is to better understand the social media presence-building strategies that brands might use, as well as how these strategies may directly influence millennials' likelihood to buy throughout Coivd-19. In order to discover trends and formulate expectations, this study uses quantitative approaches to collect and analyse data. Descriptive statistics, the Pearson Correlation Coefficient, and stepwise multiple linear regression analysis will all be used in the analysis, which will be done using a questionnaire. In this study, the purpose was evaluated using a total of five elements, including information sharing, trustworthiness, expertise, entertainment, and electronic word of-mouth (eWOM).